THE IMPACT OF THIN CAPITALIZATION RULES AS A TOOL OF TAX AVOIDANCE ON TAX REVENUE - Ferry Irawan; Ragil Novitasari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze the practice of thin capitalization in manufacture and retail companies registered in the Indonesia Stock Exchange from 2015 until 2018. The research is conducted by using quantitative methods. The sample selection uses a purposive sampling method. The research sample consists of 132 manufacturing and 18 retail companies. The research begins by examining the effect of thin capitalization on tax avoidance, then by looking for the effect of the practice of thin capitalization as a means of tax avoidance on state tax revenue. The result of research shows that thin capitalization has different effects on two business sectors, namely positive effect on manufacturing company tax avoidance and negative effect on retail company tax avoidance. Thin capitalization has no effect on the relation between tax avoidance and tax revenue.